2008
DOI: 10.1038/sj.ejhg.5201999
|View full text |Cite
|
Sign up to set email alerts
|

The VNTR 2 repeat in MAOA and delinquent behavior in adolescence and young adulthood: associations and MAOA promoter activity

Abstract: Genetic studies of delinquent and criminal behavior are rare in spite of the wide recognition that individuals may differ in their propensity for delinquency and criminality. Using 2524 participants in Add Health in the United States, the present study demonstrates a link between the rare 2 repeat of the 30-bp VNTR in the MAOA gene and much higher levels of self-reported serious and violent delinquency. The evidence is based on a statistical association analysis and a functional analysis of MAOA promoter activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 36 publications
4
107
1
3
Order By: Relevance
“…While Sabol et al [1998] found that the individuals with the 5-repeat allele have a lower transcriptional efficiency than those with 3.5-or 4-repeat allele. The 2-repeat sequence in the MAOA gene promoter is reported to display the lowest level of transcription activity, as compared with the other alleles [Guo et al, 2008].…”
Section: Neuropsychiatric Geneticsmentioning
confidence: 96%
“…While Sabol et al [1998] found that the individuals with the 5-repeat allele have a lower transcriptional efficiency than those with 3.5-or 4-repeat allele. The 2-repeat sequence in the MAOA gene promoter is reported to display the lowest level of transcription activity, as compared with the other alleles [Guo et al, 2008].…”
Section: Neuropsychiatric Geneticsmentioning
confidence: 96%
“…According to Sabol et al [80] and Decker et al [81], the product of the MAOA-VNTR can be five alleles consisting of 2, 3, 3.5, 4, and 5 30-bp tandem repeats. The relatively rare VNTR allele with 2 repeats displays the lowest expression of the enzyme, corresponding only to 25-30% of the activity of the MAOA promoter in allele 4 [82]. When this allele was present, a two-fold increased level of delinquency and violent delinquency compared to the carriers of other MAOA-VNTR variants in men, and similar although weaker symptoms in women, were observed [82].…”
Section: Monoamine Oxidasementioning
confidence: 97%
“…The relatively rare VNTR allele with 2 repeats displays the lowest expression of the enzyme, corresponding only to 25-30% of the activity of the MAOA promoter in allele 4 [82]. When this allele was present, a two-fold increased level of delinquency and violent delinquency compared to the carriers of other MAOA-VNTR variants in men, and similar although weaker symptoms in women, were observed [82]. It has been known that allele 2 of the MAOA-VNTR represents the most "criminogenic" variant of monoamine oxidase A.…”
Section: Monoamine Oxidasementioning
confidence: 99%
“…PCR products consist of five fragment sizes, including 2, 3, 3.5, 4 or 5 copies of the repeated sequence; the 3.5R and 4R copies are transcribed more efficiently than the 2R, 3R or 5R, while 2R exhibits the lowest promoter activity (Sabol et al 1998); an association of the 2R variant with delinquent behavior in adolescence has been suggested (Guo et al 2008). …”
Section: Modulation Of Mao-a Expression In Neuropsychiatric Disordersmentioning
confidence: 99%